2019
DOI: 10.7150/thno.33598
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti-DR5 antibody-drug conjugate possesses a high-potential therapeutic efficacy for leukemia and solid tumors

Abstract: It is well known that tumor necrosis factor-related apoptosis inducing ligand receptor 1 or 2 (DR4/DR5) is specifically expressed in various tumor cells, but less or no expression in most normal cells. Many first generations of TRAIL agonists including recombinant preparations of TRAIL, agonistic antibodies against DR4/DR5 have been developed in phase I/II clinical trials for cancer therapy. However, the outcomes of clinical trials by using DR4/DR5 agonist mono-therapy were disappointed even though the safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Since DcR-2 and TRAIL-R2 are coexpressed in HNSCC tumors (60), the efficacy of TRAILmediated HNSCC therapy needs validation (34,35). As the resistance to TRAIL seems to exist in most tumor cells (33)(34)(35), the trials of newly developed anti-TRAIL-R2-drug conjugate reagents coupling with anti-miR-372 strategies could be elaborated as a potent therapeutic approach with the aim of ameliorating oncogenesis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since DcR-2 and TRAIL-R2 are coexpressed in HNSCC tumors (60), the efficacy of TRAILmediated HNSCC therapy needs validation (34,35). As the resistance to TRAIL seems to exist in most tumor cells (33)(34)(35), the trials of newly developed anti-TRAIL-R2-drug conjugate reagents coupling with anti-miR-372 strategies could be elaborated as a potent therapeutic approach with the aim of ameliorating oncogenesis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…As TRAIL-R1 and TRAIL-R2 are apoptosis triggers that are active specifically in cancer cells rather than healthy cells (31,32), TRAIL-based therapies have become potential cancer targeting strategies. However, targeting TRAIL has disappointing outcomes because resistance to TRAIL therapy is common in cancers (33)(34)(35)(36). Specifically, a previous study Abbreviations: BrdU, 5-bromo-2 ′ -deoxyuridine; CDDP, cisplatin; ChIP, Chromatin immunoprecipitation; DMOG, dimethyloxaloylglycine; EMT, epithelial-mesenchymal transition; FPKM, fragments per Kb of transcript per million mapped reads; HNSCC, head and neck squamous cell carcinoma; LATS2, large tumor suppressor kinase 2; miRNA, microRNA; MMP, mitochondrial membrane potential; Mut, mutation; NCMT, non-cancerous matched tissue; OSCC, oral squamous cell carcinoma; qRT-PCR, quantitative reverse transcription polymerase chain reaction; TCGA, The Cancer Genome Atlas; TRAIL, tumor necrosis factor related apoptosis-inducing ligand; TRAIL-R1, tumor necrosis factor related apoptosis-inducing ligand receptor 1; TRAIL-R2, tumor necrosis factor related apoptosis-inducing ligand receptor 2; WT, wild type; ZBTB7A, zinc finger and BTB domain containing 7A.…”
Section: Introductionmentioning
confidence: 99%
“…And it does not have notable toxic side effects on heart, liver, lung and kidney. [ 175 ] Lung cancer Mouse PG545 was highly effective in PDX that did not respond to conventional chemotherapy (cisplatin), while other PDX tumors responded well to cisplatin and to a lower extent to PG545. [ 176 ] Lung cancer Rat The severely immunodeficient SD‐RG rats support fast growth of PDX compared with mice, thus holding great potential to serve as a new model for oncology research.…”
Section: Patient-derived Tumor Xenograft (Pdx) Modelmentioning
confidence: 99%
“… 24 , 25 In a previous study, we first reported that a novel highly potent first-in-class ADC named Zapadcine-1 can effectively target DR5 and displays an excellent antitumor activity against both solid tumors and hematological malignancies, but the therapeutic window of this ADC was markedly lower for effective human cancer therapy. 26 …”
Section: Introductionmentioning
confidence: 99%
“…Oba01 utilizes the humanized DR5-specific monoclonal antibody zaptuzumab coupled via a cleavable linker to a highly toxic inhibitor of tubulin, monomethyl auristatin E (MMAE), by using ThioBridge technology. 26 , 27 We explored its possible anti-tumor efficacy in both in vitro and in vivo models. The toxicity and pharmacokinetic (PK) analysis of Oba01 demonstrated excellent safety, stability, and tolerability in both Sprague-Dawley (SD) rats and cynomolgus monkeys, indicating that Oba01 can potentially act as an attractive therapeutic candidate for further clinical investigation in patients with DR5-positive ALL.…”
Section: Introductionmentioning
confidence: 99%